Nomadism Now: Cultural Survival in a Changing Desert Environment - Robbins, Paul (Annals of Arid Zone, 2016)
While the demise of nomadic pastoralism in South Asia and elsewhere has been long predicted, its persistence is a fact of life throughout the arid zone. This essay revicws the way in which nomadic livelihoods have evolved in the last twenty years, as has thinking and writing about them, with. attention to the situation in India in a comparative global context. The review emphasizes that itinerant ecologies and polities are more complex and adaptive than previously understood, and' that recent pastoral development practice has changed and been changed by nomadic peoples themselves. The essay ends with a discussion of the most serious and overlooked barriers to the survival of mobile adaptations and cultures, which include: innovations in conservation tillage, expansion of invasive species, and potential changes in the structure of the meat and dairy economy.